Probabilistic analysis of ambiguities in radar echo direction of arrival from meteors - Kastinen, Daniel; Kero, Johan (Swedish Institute of Space Physics, 2020)
In this study we examined how the direction of arrival determination of meteor radar echoes behaved in collection of interferometric radar system. These methods are general and can be applied on any system, we chose five radar systems currently used to perform meteor studies. Specifically we examine when and if the direction of arrival is of ambiguous and with what probability it occurs as a function of signal to noise ratio.

See the readme file for description of the content.

I denna studie var målet att kartlägga hur bestämningen av infallsvinklar för radar ekon från meteorer beter sig för några interferometriska radar system. Metoderna är generella och vi applicerade dem på fem olika system. Specifikt var vi intresserade av att klassificera när och om det fanns tvetydiga lösningar och vilken sannolikhet de hade att uppenbara sig baserat på signal brus förhållandet.

See "readme.txt" filen för beskrivning av variabler och innehåll.
Sannolikhetsfördelningen av tvetydiga infallsvinklar för radar ekon från meteorer
Keywords: radar; radar; meteor; meteor; Interferometry; interferometri; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap